PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI - Pritilim; Vargo Christian L. Tobing (SCIENTIA JOURNAL, 2022)
This study discusses how important Intellectual Intelligence, Emotional Intelligence, and Learning Behavior in understanding accounting. A questionnaire is used to collect data. The sample for this study was chosen using simple random sampling. The questionnaire was given out to accounting students with 286 responden. Methods of data processing are used multiple linear regression analys with help of SPSS (Product Statistics and Service Solutions). The outcome of this research partially indicate that Intellectual Intelligence and Emotional Intelligence has affect a significant possitive effect on understanding accounting. Learning Behavior has not affect and not significant on understanding accounting. However, simultaneously the variables Intellectual Intelligence, Emotional Intelligence, and Learning Behavior have significant effect on understanding accounting.